Taqnīn Method of Qānūn Jināyah and Problems of Its Implementation in Aceh, Indonesia - Sakhowi, Sakhowi (Institut Agama Islam Negeri (IAIN) Pontianak, 2022)
Since its emergence during the Abbasid period, the idea of taqnīn fiqh (codification of Islamic jurisprudence) has caused controversy. The controversy is getting more complex with the ratification of Aceh Qanun No. 6 of 2014 on Jinayat Law (Islamic criminal law) in Indonesia, which is not an Islamic country. This article aims to analyze the taqnīn method and the problems of implementing the Qānūn Jināyah in Aceh. This article is library research using content analysis. The author found that the Qānūn Jināyah in Aceh, seen from the taqnīn ‘Abd al-Bar method, in terms of its coverage area, is included in the mandatory qaḍā’ (māliyyah, syakhṣiyyah, and jinā’iyyah) namely problems that have the character to be resolved in court. In its source, the Qānūn Jināyah uses the dominant regional school of thought (Syafī’ī’s school) and other schools if there is a benefit, but only as an alternative. In its implementation, the Qānūn Jināyah caused controversy even though Aceh received regional autonomy and the Qānūn Jināyah was under juridical regulations. Its presence is still not accepted by numerous groups, both from within and outside. Enforcement of Qānūn Jināyah, such as caning, is considered a violation of human rights. The Qānūn Jināyah tends to discriminate against women, non-Muslims and the poor. The assessment that the qānūn violates human rights is from a different perspective. In the legal-normative context, the qānūn is legally valid in Indonesia in terms of procedure and substance because it has gone through the correct manufacturing process and has gone through the evaluation stage by the central government.